Imido-P(V) trianion supported enantiopure neutral tetrahedral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Paithankar, Harshad; Chugh, Jeetender; Steiner, Alexander; Boomishankar, Ramamoorthy (Chemical Communications, 2018)
Charge-neutral chiral hosts are attractive due to their ability to recognize a wide range of guest functionalities and support enantio-selective processes. However, reports on such charge-neutral cages are very scarce in the literature. Here, we report an enantiomeric pair of tetrahedral Pd(II) cages built from chiral tris(imido) phosphate trianions and oxalate linkers, which exhibit enantioselective separation capabilities for epichlorohydrin, beta-butyrolactone, and 3-methyl- and 3-ethyl cyclopentanone.

Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.

Squarate-tethered enantiomeric Imido-Pd(II) cages for recognition and separation of chiral organic molecules - Jose, Cavya; Sarkar, Meghamala; Rajasekar, Prabhakaran; Tewari, Tanuja; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2023)
Chiral coordination cages have emerged as an efficient platform for enantioselective processes via host-guest interactions. Here, we report an enantiomeric pair of tetrahedral cages of formula [(Pd-3[PO(N(*CH(CH3)Ph)(3)])(4)(C4O4)(6)] supported by chiral tris(imido)phosphate trianions and squarate (C4O4)(2-) linkers. These cages exhibit unusual coordination isomerism for Pd(II)-linker bonds compared with the other Pd(II) cages of this family. Further, they were employed for the recognition and separation of small chiral molecules containing various functionalities. High enantioselectivities of 67 and 41 were found in the case of R-4-hydroxydihydrofuran-2(3H)-one and S-epichlorohydrin, recognized by the R-isomer of the cage. Chiral separation studies showed remarkable enantiomeric excess values of 93 and 85% for S-epichlorohydrin and R-4-benzyl-2-oxazolidinone, respectively, from their racemic mixtures. These studies showcase the potential of coordination cages for enantioselective applications.